Global disease burden of interstitial lung disease and pulmonary sarcoidosis, 1990-2021, and forecast analysis over the next decade - Li, Xinlian; Zhang, Zhihong (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Interstitial lung disease is a major class of disease that affect lung health, however, there is a lack of epidemiological studies related to the global burden of this disease. Data from the Global Burden of Disease Study 2021 (GBD 2021) were utilized to evaluate the global burden of interstitial lung disease and pulmonary sarcoidosis comprehensively in 21 global regions, 204 countries and territories from 1990 to 2021, examining their association with the sociodemographic index, and forecasting trends for the forthcoming decade. Methods: Using GBD 2021 data, we analyzed interstitial lung disease and pulmonary sarcoidosis prevalence, incidence, mortality, and disability-adjusted life years. We calculated age-standardized rate trends (1990–2021) through generalized linear models and assessed disease burden inequalities using the sociodemographic index, slope index, and concentration index. Global maps and regional comparisons visualized burden distribution. Decomposition analysis quantified impacts of population growth, aging, and epidemiological changes. Future burden trends (next decade) were projected using Bayesian Age-Period-Cohort modeling. Results: From 1990 to 2021, the global burden of interstitial lung disease and pulmonary sarcoidosis has been on the rise. Generally, Higher age‐standardized rates of interstitial lung disease and pulmonary sarcoidosis were observed in higher age groups and areas with a high socio-demographic index. Moreover, population growth and ageing are the main causes of the increased burden of disease. Projections indicate that by 2034, the number of cases, illnesses, deaths, and disability-adjusted life years associated with interstitial lung disease and pulmonary sarcoidosis will continue to rise, while age-standardized rates are expected to plateau. Conclusions: The global disease burden of interstitial lung disease and pulmonary sarcoidosis remains significant and deserves our attention. People aged 70-84 and high sociodemographic index group should be the focus of attention.